العمارة الدينية في مدينة (دور) كوريكالزو - محان, محمد سياب; كاظم, حسين شهيد (Journal of College of Education, 2018)
It is possible to say that after presenting a description of the religious architecture of Dur- Kurekalzu, that the Kassite were clearly influenced by the religion of Mesopotamia. Despite the simple developments they have made in the field of the stairs of the zakora and terraces, which represented two unique cases that did not exist previously, There is a kind of evolution of the religious architecture in this city that represents them, as can be inferred through the allocation of the temples of the goddess of ancient Mesopotamia, and quote many of the architectural details of the building.                   .